Practical experience of allergy to egg proteins clinical manifestation - Maria Zofia Lisiecka (PAGEPress Publications, 2024)
Food allergy occupies a significant place among disorders that impair the quality of patients' lives, bringing a large number of restrictions to their diet and lifestyle. Therefore, the purpose of this study is to examine the clinical features of allergy to chicken eggs with the determination of key trends in diagnosis and treatment. A descriptive and comparative analysis of three cases was carried out with a large-scale assessment of specific Immunoglobulins E (IgE), determined by the enzyme-linked immunosorbent assay. It becomes clear, that due to the high prevalence of allergy to white and yolk of chicken eggs in the general population (among the Polish population including), chicken eggs have severe allergenic characteristics and may display various symptoms that may be problematic to differentiate. The patients from the presented cases were characterized by a severe course of the disease - minimal consumption of chicken eggs led to the development of urticaria, swelling of the eyelids, and bronchospasm, which required urgent administration of adrenaline and hospitalization. For the purpose of diagnosis, patients with anaphylactic reactions are highly restricted, because methods of skin prick testing, and provocation tests (oral and nasal) are contraindicated. In this regard, molecular diagnostics and the determination of specific immunoglobulins E for ovalbumin, ovomucoid, and other glycoproteins are recommended. This research can lead to the creation of purified recombinant allergens for use in the process of diagnosis and treatment, as well as in the food industry, also, it emphasizes the introduction of preventive measures for the development of anaphylaxis.